'Now the salvation of our God has come ...' a narrative perspective on the hymns in Revelation 12-15 - Du Rand, Jan A. (Neotestamentica, 1993)
The hymns in the Apocalypse of John function as interpretative commentary on decisive events in the unfolding of the plot. From narratological perspective, it is clear that the reader becomes involved in responsive worshipping through association with the hymns. The reader, representing the faithful, experiences a catharsis in associating with the hymns, to live from the perspective that God's kingly rule is visually manifested through the decisive Christ-event. From an analysis of 12:10-10 and 15:3-4 it becomes even more clear that the struggle between good and evil, represented spatially in heaven and on earth respectively has been won by God. Therefore, the faithful have reason to praise God for his deeds, ways and righteous acts and the fact that his kingly rule and salvation have arrived on earth.